POTENSI PSIKOLOGIS DALAM MENDIDIK SANTRI MENURUT AL-GAZA>LI - Khasan Ubaidillah (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2013)
As the children learning practices in the national learning system do not consider physical and spiritual dimensions, it can not lead to a humanist learning system, even it may be said as un-Islamic. Is Gaza>li>, a classical Islamic education leaders who offer the concept of human potential that can sinergize the two-dimensional requirements of human. Based on this, this article intends to study and applying the concepts of learning students. By using a descriptive analysis of the literature owned by Gaza>li> it is found that human potential consists of the potential birth (al-h{iss al-khams) and the inner potential (al-khaya>l, at-tafakkur, al-khifz{, at-taz|akkur dan al Musytarak). According to him, these two potentials have their different functions each of which greatly affect the learning process of students. Furthermore, the thesis Gaza>li> This was the same even able to integrate the theories of modern cognitive psychology and behavioral education.